2017
DOI: 10.1155/2017/8450618
|View full text |Cite
|
Sign up to set email alerts
|

Legume Consumption and All-Cause and Cardiovascular Disease Mortality

Abstract: Background Legume consumption is suggested to have protective effects against cardiovascular disease (CVD) mortality in the general population, but the results have been equivocal. We conducted a meta-analysis of prospective cohort studies to assess the association between legume consumption and risk of CVD mortality and all-cause mortality. Methods and Results Medline (via Ovid) and EMBASE (via Ovid) databases were searched through April 2017 to identify eligible studies. The two authors independently extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 31 publications
2
23
0
1
Order By: Relevance
“…However, if phosphorus intake is associated with an increased and mainly plantderived protein intake-where bioavailability of phosphorus tends to be lower 98 -the association of serum phosphorus and mortality might look different as consumption of many vegetables containing high amounts of phosphorus and protein such as legumes may be associated with lower all-cause mortality, at least in the general population. 99 Another important aspect of plant-derived phosphorus intake and the use of phosphate binders is how they might affect gut microbiota potentially influencing intestinal permeability, gut-derived uremic toxins levels, endotoxin levels, and inflammation in chronic renal disease, issues that remain insufficiently studied. In the meantime, a thorough dietary assessment remains our only chance to sort out these complex relationships in an individual patient.…”
Section: Invited Editorialmentioning
confidence: 99%
“…However, if phosphorus intake is associated with an increased and mainly plantderived protein intake-where bioavailability of phosphorus tends to be lower 98 -the association of serum phosphorus and mortality might look different as consumption of many vegetables containing high amounts of phosphorus and protein such as legumes may be associated with lower all-cause mortality, at least in the general population. 99 Another important aspect of plant-derived phosphorus intake and the use of phosphate binders is how they might affect gut microbiota potentially influencing intestinal permeability, gut-derived uremic toxins levels, endotoxin levels, and inflammation in chronic renal disease, issues that remain insufficiently studied. In the meantime, a thorough dietary assessment remains our only chance to sort out these complex relationships in an individual patient.…”
Section: Invited Editorialmentioning
confidence: 99%
“…Breast cancer and colorectal cancer are the leading causes of global cancer‐related mortality with approximately 1.2 million new cases being registered each year (Jemal et al, ). Meta‐analyses of cancer prevalence and diet reveal a negative, dose‐dependent correlation between legume intake and colorectal cancer risk (Clemente & Olias, ), with a 100g weekly legume intake being suggested as a robust protective measure against these cancer types (Li, Li, Shen, Wang, & Zhou, ).…”
Section: The Benefit Of Legumesmentioning
confidence: 99%
“…Meta-analyses of cancer prevalence and diet reveal a negative, dose-dependent correlation between legume intake and colorectal cancer risk (Clemente & Olias, 2017), with a 100g weekly legume intake being suggested as a robust protective measure against these cancer types (Li, Li, Shen, Wang, & Zhou, 2017).…”
Section: Legumes and Healthmentioning
confidence: 99%
“…A systematic review and meta-analysis study involving 367,000 individuals with 18,475 cases of cardiovascular events (7,451 acute myocardial infarction and 6,336 cases of cerebral infarction) demonstrated that high legume consumption was associated with a significant 10% reduction in cardiovascular mortality and acute myocardial infarction. When the consumption of legumes and cerebral infarction was analyzed separately, no significant relationship was found 34 , however the evidence shows that the consumption of legumes is beneficial to reduce all-cause mortality 35 . We believe that currently, studies are still necessary that consider the type, quantity, optimal intake and frequency of consumption of legumes and their relationship with cardio-metabolic diseases.…”
Section: Consumption Of Andean Legumes and Risk Of Cardio-metabolic Dmentioning
confidence: 93%